Solomon Islands Folk Taxonomy of Fish Species - Sebastian C A Ferse; Shankar Aswani (PANGAEA, 2020)
This table contains locally-recognized names of marine fish species from Roviana Lagoon, Western Province, collected in 2014-2015 from four communities (Ilangana, Nusa Roviana, Baraulu and Nusa Hope) in eight focus groups per community, covering four age groups (13-19, 20-35, 36-55 and >55 years) for both men and women (rows 3-34). The table furthermore contains species names collected from multiple communities across Roviana Lagoon in 1992-1995, published previously in Aswani 1997. The data is organized with species names, samples and code of sites, corresponding to gender, age group and community, in one column each.